2000
DOI: 10.1103/physrevb.62.4698
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and adhesion of Nb/sapphire: The effect of oxygen partial pressure

Abstract: We derive a formula, useful for first-principles calculations, which relates the free energy of an oxide/metal interface to the free energies of surfaces and the work of separation of the interface. We distinguish the latter mechanical quantity from the thermodynamic work of adhesion, and we describe explicitly how both may be calculated. Our formulae for interfacial and surface energies are cast in terms of quantities which can be calculated or looked up in tables, and include as additional parameters the amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
150
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(162 citation statements)
references
References 50 publications
11
150
1
Order By: Relevance
“…21) and Nb/Al 2 O 3 (Ref. 22). We note that the computed energies for the OO-terminated case, ∼ 4 J/m 2 , are consistent with values obtained experimentally by Kriese et al 6 for 100 nm thick films of Cu on SiO 2 using an indentation technique.…”
Section: Quantitative Analysis Of Adhesionsupporting
confidence: 75%
See 1 more Smart Citation
“…21) and Nb/Al 2 O 3 (Ref. 22). We note that the computed energies for the OO-terminated case, ∼ 4 J/m 2 , are consistent with values obtained experimentally by Kriese et al 6 for 100 nm thick films of Cu on SiO 2 using an indentation technique.…”
Section: Quantitative Analysis Of Adhesionsupporting
confidence: 75%
“…A first principles treatment would therefore be most appropriate for examining the nature of local bonding at an ideal interface between the two systems, and indeed this approach has proved insightful in the past for studying adhesion between metal films and insulating substrates. [21][22][23][24] Previous first-principles work on the α−quartz surface 20 observed significant changes in bonding near the surface; to our knowledge, however, the effects of metallic overlayers on SiO 2 surface geometries and electronic properties have yet to be examined from first principles.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wang et al 15 showed that the single Al-terminated surface is stable up to high oxygen partial pressures with large inward relaxations, but that the O-terminated surface can be stabilized by hydrogen. Other calculations have confirmed that hydrogen strongly affects the surface, 3,[16][17][18] and different terminations of the clean and hydrated surface have also been observed experimentally. 19 Moreover, the dissociation mechanism of water on the surface has been thoroughly investigated, and H 2 O has been shown to dissociate readily.…”
Section: Introductionmentioning
confidence: 58%
“…The formalism we use here is already well established in the surface science community ("ab initio thermodynamics"), and a very detailed discussion can be found in previous work. 3,19,20 In the following, we will briefly introduce the main equations (for further reading, we refer to Refs. 3, 20, and 21).…”
Section: B Thermodynamics Of the (0001)-o Surfacementioning
confidence: 99%